Accessing the distance range of interest in biomolecules: Site-directed spin labeling and DEER spectroscopy. Issue 3 (2010) - Böhme, Sabine; Steinhoff, Heinz-Jürgen; Klare, Johann P.
Abstract : Investigations on the structure and function of biomolecules often depend on the availability of topological information to build up structural models or to characterize conformational changes during function. Electron paramagnetic resonance (EPR) spectroscopy in combination with site–directed spin labeling (SDSL) allow to determine intra- and intermolecular distances in the range from 4–70 Å, covering the range of interest for biomolecules. The approach does not require crystalline samples and is well suited also for molecules exhibiting intrinsic flexibility. This article is intended to give an overview on pulsed EPR in conjunction with SDSL to study protein interactions as well as conformational changes, exemplified on the tRNA modifying enzyme MnmE.